Why are trade agreements more attractive in the presence of foreign direct investment? - Marcelo Olarreaga (World Trade Organization (WTO), 1998)
This paper argues that interests of nationals and owners of home-based foreign capital in the formation of a Trade Agreements (TA) are not antagonistic, except under rather particular assumptions on initial tariffs among potential members. Further, if initial tariffs are endogenously determined through an industry-lobbying process, then TA that would have been immiserising in the absence of Foreign Direct Investment (FDI), may be welfare-enhancing in the presence of foreign-owned firms. The rationale is linked to the effect that the entry of FDI has on the pre-TA tariff, through contributions to the incumbent government. These results may help explain recent integration programs between developed and developing countries.
Keywords: F12; F15; F23; 330; Trade Agreement; Foreign Direct; Political Economy